Updating the Occurrence of the Soil Liquefaction Phenomenon in Peru - Alva Hurtado, Jorge Elias Domingo (2020)
We present the information available on the phenomenon of soil liquefaction in Peru due to the seismic action and its representation in a map of soil liquefaction areas. The map of soil liquefaction areas is drawn to the scale 1: 5'000,000 and presents distinctions between liquefaction and probable liquefaction cases, according to the interpretation of the information available in the literature. All the documentation that presents evidence of the phenomenon of liquefaction, such as the formation of small volcanoes of mud and sand, the violent expulsion of water from the soil, the presence of intense cracking and the differential settlements due to the seismic action, has been detailed in this article.